Surgical hip dislocation for posterior hip dislocation with femoral head fracture pipkin classification type II: A case report - Siregar, Chairiandi; Rambe, Syahrul Ramadan; Renaldi, Rizal (Jurnal Prima Medika Sains, 2024)
Introduction: Surgical hip dislocation is a powerful and safe approach. It allows for simultaneous treatment of intra-articular pathologies, either preexisting or as a result of trauma, and improves long-term results. It can be used to treat a wide variety of intra-articular pathologies that would be extremely challenging or impossible arthroscopically or with other common open approaches to the hip. Surgical hip dislocation has been used in the trauma setting for open reduction and internal fixation of femoral head fractures and posterior wall acetabular fractures that do not extend into the posterior column. Case Report: A 28-year-old male with a posterior hip dislocation had difficulty flexing and extending his hip, internal rotation, and shortening his leg. During physical examination, we found a prominent head left femur on the posterior gluteus. During an X-ray examination, we found a posterior dislocation of the femoral head with a fracture. Treatment: Open reduction is preferable whenever there is a nonconcentric hip reduction. This reduces the risk of additional trauma, thus avoiding abrasion to the articular cartilage and bone contusion at the head of the femur. The surgeon who performs open reduction must be fully familiar with the surgical anatomy of the hip and must be aware of the fixation techniques used on fractures in this region. The fragment can be fixed both with 2.0-mm Herbert screws or mini fragment screws, taking care of the head of the implant into the articular cartilage. The joint capsule should always be repaired. When femoral head impaction is present, and the patient is an adult, the goal is to save the femoral head. In this situation, it is preferable to use the Watson-Jones or anterolateral approach with greater trochanteric osteotomy to perform the controlled dislocation of the hip.